2010
DOI: 10.1007/s10404-010-0637-9
|View full text |Cite
|
Sign up to set email alerts
|

Mixing speed-controlled gold nanoparticle synthesis with pulsed mixing microfluidic system

Abstract: Gold nanoparticles with diameters of a few tens of nanometer and a narrow size distribution were synthesized using a pulsed mixing method with a microfluidic system which consists of a Y-shaped mixing microchannel and two piezoelectric valveless micropumps. This mixing method enables control of the mixing speed of gold salts and reducing agent by changing the switching frequency of the micropumps, which was our focus to improve the particle size distribution, which is an essential parameter in gold nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…Under the reasonable structural parameters and control parameter condition, a thinner pulsating layer can be formed in the micromixing channel. It can effectively increase the contact area and contact opportunity between the solutions, shorten the mixing time, and greatly improve the mixing effect between three solutions [17,24,25]. Figure 2(b) is the schematic diagram of experimental scheme, A represents the glucose (C 6 H 12 O 6 ) solution, C represents the silver nitrate (AgNO 3 ) solution containing PVP, and B represents the sodium hydroxide (NaOH) solution.…”
Section: Controllable Synthesis Of Agnpsmentioning
confidence: 99%
“…Under the reasonable structural parameters and control parameter condition, a thinner pulsating layer can be formed in the micromixing channel. It can effectively increase the contact area and contact opportunity between the solutions, shorten the mixing time, and greatly improve the mixing effect between three solutions [17,24,25]. Figure 2(b) is the schematic diagram of experimental scheme, A represents the glucose (C 6 H 12 O 6 ) solution, C represents the silver nitrate (AgNO 3 ) solution containing PVP, and B represents the sodium hydroxide (NaOH) solution.…”
Section: Controllable Synthesis Of Agnpsmentioning
confidence: 99%
“…Thus, many researchers have adopted the use of microreactors for the production of citrate-capped gold nanoparticles. In most cases researchers take advantage of better mixing in different types of microreactors (Kumar et al, 2014;Liu et al, 2015;Sugano et al, 2010;Yang et al, 2010) in order to reduce the polydispersity of synthesized gold nanoparticles and tune the particle size by parameter optimization (Lohse et al, 2013). Nonetheless, without strong reducing agents, faster mixing itself cannot fundamentally increase nucleation rate.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 2B, it was observed that the λ max value obtained is between 480 and 490 nm for all cases at different flow rates in AFR™ in the presence of CTAB surfactant. The heartshaped design in AFR™ gives superior mixing, however, the residence time is higher in the case of AFR™ as compared to the MR and hence the particle size was higher in the case of AFR™ as compared to the MR and also the PSD was more wider in the case of AFR™ as compared to the MR. Due to the higher residence time in AFR™ higher extent of crystal growth of NPs occurs after short nucleation time resulting in higher size and also wider distribution [53][54][55][56]. From the data obtained for the UV absorbance spectra and average particle size (Table 1), it was established that the iron oxide NPs prepared in AFR™ have higher particle size compared to that obtained in the case of the MR, attributed to higher residence time in AFR™.…”
Section: Reaction Mechanism For the Formation Of Iron Oxide Nanopartimentioning
confidence: 79%
“…The changes in the mixing patterns and its intensity affect the nucleation, formation and growth of the iron oxide NPs, in turn, affecting the size and poly-dispersity of the obtained NPs. Further the mixing pattern in the reactor plays an important role in the process of nanoparticle formation in different types of reactors, affecting the particle size, PSD, and stability of iron oxide NPs which in turn affects the obtained zeta potential values [53,57].…”
Section: Zeta Potential Analysis For Particles Obtained In Microreactmentioning
confidence: 99%